A Review of 3D Printing Technology for Medical Applications. (October 2018) - Yan, Qian; Dong, Hanhua; Su, Jin; Han, Jianhua; Song, Bo; Wei, Qingsong; Shi, Yusheng
Abstract: Donor shortages for organ transplantations are a major clinical challenge worldwide. Potential risks that are inevitably encountered with traditional methods include complications, secondary injuries, and limited source donors. Three-dimensional (3D) printing technology holds the potential to solve these limitations; it can be used to rapidly manufacture personalized tissue engineering scaffolds, repair tissue defects in situ with cells, and even directly print tissue and organs. Such printed implants and organs not only perfectly match the patient's damaged tissue, but can also have engineered material microstructures and cell arrangements to promote cell growth and differentiation. Thus, such implants allow the desired tissue repair to be achieved, and could eventually solve the donor-shortage problem. This review summarizes relevant studies and recent progress on four levels, introduces different types of biomedical materials, and discusses existing problems and development issues with 3D printing that are related to materials and to the construction of extracellular matrix in vitro for medical applications.